Simulation of additive metal printing top layer distortion - Low, Lionel Aik Hong (Nanyang Technological University, 2020)
Additive Manufacturing is widely used in many industries with its huge potential in a variety of applications. Selective Laser Melting (SLM) Powder Bed Fusion, is one of many additive manufacturing processes capable of 3D printing metal components with complex geometries. This process surpasses conventional methods in many ways. A typical application is cages used in the control valves industry. Some of the complicated problems involving SLM Powder Bed Fusion are thermal defects like warpage. The effects of thermal defects vary according to shapes, sizes and materials. The behavior and trend of thermal defects must be studied to help understand the problems faced in Powder Bed Fusion processes.